Developing students’ strategies for problem solving in mathematics: the role of pre-designed “Sample Student Work” - Evans, Sheila; Swan, Malcolm (International Society for Design and Development in Education, 2014)
This paper describes a design strategy that is intended to foster self and peer assessment and develop students’ ability to compare alternative problem solving strategies in mathematics lessons. This involves giving students, after they themselves have tackled a problem, simulated “sample student work” to discuss and critique. We describe the potential uses of this strategy and the issues that have arisen during trials in both US and UK classrooms. We consider how this approach has the potential to develop metacognitive acts in which students reflect on their own decisions and planning actions during mathematical problem solving.